Model Environment-Behavior dalam Manajemen Kelas untuk Mendukung Perkembangan Kognitif dan Interaksi Sosial Anak Usia Dini - Istifadah Istifadah; Lailatul Usriyah; Riyas Rahmawati; M. Andya Duta Ardha; A. Ditya Akbar Wiranegara (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2026)
The learning environment plays a crucial role in supporting early childhood development, yet classroom management in many early childhood education institutions still emphasizes administrative functions rather than optimizing the physical and social environment as an integral part of pedagogy. This study examined the implementation of the Environment–Behavior model in classroom management and its implications for children's cognitive development and social interaction. A qualitative multi-site case study was conducted at Sekolah Alam Bunda Preschool (SABP) and Sekolah Alam Nurul Islam (SANI), Jember Regency, Indonesia. Data were collected through participant observation, in-depth interviews, and document analysis involving six purposively selected informants until data saturation was achieved. Trustworthiness was established through triangulation and member checking, while data were analyzed using the interactive model of Miles, Huberman, and Saldaña, followed by cross-site analysis. The findings indicate that a safe, flexible, and nature-based learning environment enriched with sensory experiences enhances children's observation, exploration, simple problem-solving, and active learning engagement. It also promotes communication, collaboration, prosocial behavior, and self-regulation, although some children required an adaptation period and teacher guidance. The study proposes an Environment–Behavior conceptual model that integrates five interconnected dimensions—physical environment, sensory experiences, exploration, social interaction, and self-regulation—as a pedagogical system supporting holistic child development. These findings extend ecological pedagogy and provide practical guidance for designing adaptive, child-centered learning environments.